Analysis of the location of the installation of cellular towers by the method Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER) - Putra Edi Mujahid; Ryan Chandra; Andri Syahputra Tarigan; Maya Frida Panjaitan (Sean Institute, 2022)
Cellular is the most important thing for today's society. For this reason, a strong signal is a priority as a means that must exist to support the cellular to work properly. Installation of cellular towers for the need for strong signal is important. PT. Solusi Tunas Pertama is a company engaged in cellular tower construction services. The problem found is that it is difficult to determine the right tower installation due to the conditions and environment as well as the impact of the cellular tower. For this reason, an analysis is needed in determining the right area for the installation of the cellular tower. In this study, the authors use the criteria of population density, distance, access, existing towers and costs. These five criteria are often used by companies for location assessment. The author uses the SMARTER method in analyzing the determination of the location of the cellular tower installation of PT. Solusi Tunas Pertama. The results obtained are that the Gunung Kiri Village area is the right location for the installation of cellular towers with a value of 60,58929 compared to other locations, namely Sisiran Forest and Balunga Rice Fields. The author conducted this research with the aim of assisting the company in determining the location of tower installation with the right confidence without the need to just guess so that the decision is not right.